Non-Steroidal Anti-Inflammatory Drugs Do Not Influence the Urinary Testosterone/Epitestosterone Glucuronide Ratio - Lundmark, Jonas; Gårevik, Nina; Thörngren, John-Olof; Garle, Mats; Ekström, Lena; Rane, Anders; Schulze, Jenny J. (Frontiers in Endocrinology, 2013)
The UDP Glucuronosyl Transferase (UGT) enzymes are important in the pharmacokinetics, and conjugation, of a variety of drugs including nonsteroidal anti-inflammatory drugs (NSAIDs) as well as anabolic androgenic steroids (AAS). Testosterone glucuronidation capacity is strongly associated with a deletion polymorphism in the UGT2B17 gene. As the use of high doses of NSAIDs has been observed in athletes there is a risk for a drug-drug interaction that may influence the doping tests for AAS. In-vitro studies show inhibitory potential on UGT2B7, 2B15 and 2B17 enzymes by NSAIDs. The aim of this study was to investigate if concomitant use of NSAIDs and a single dose of testosterone enanthate would affect the excretion rate of testosterone and epitestosterone glucuronide (TG and EG) as well as the T/E ratio, thereby affecting the outcome of the testosterone doping test. The study was designed as an open, randomized, cross-over study with subjects being their own control. The 23 healthy male volunteers, with either two, one or no allele (ins/ins, ins/del or del/del) of the UGT2B17 gene, received the maximum recommended dose of NSAID (Ibuprofen or Diclofenac) for six days. On day three, 500 mg of testosterone enanthate was administered. Spot urine samples were collected for 17 days. After a wash out period of four months the volunteers received 500 mg testosterone enanthate only, with subsequent spot urine collection for 14 days. The glucuronides of testosterone and epitestosterone were quantified. NSAIDs did not affect the excretion of TG or EG before the administration of testosterone. The concomitant use of NSAIDs and testosterone slightly increased the TG excretion while the EG excretion was less suppressed compared to testosterone use only. The effects of the NSAIDs on the TG and EG excretion did not differ between the UGT2B17 genotype groups. In conclusion, the outcome of testosterone doping tests does not seem to be affected by the use of NSAIDs.